JURIDICAL REVIEW OF THE TRANSFER OF LAND OWNERSHIP RIGHTS THAT ARE TRADED BY PLOT IN SUMBAWA REGENCY - Elma Apriani; Hilman Syahrial Haq; M. Taufik Rachman (Media Keadilan: Jurnal Ilmu Hukum, 2024)
The research entitled "Juridical Review of Transfer of Land Ownership Rights in Kapling in Sumbawa Regency" aims to find out the process of transferring land ownership rights that are traded in kapling at the Sumbawa district land office, to find out the legal certainty of ownership of land plots that are traded in Sumbawa district. The approach methods in this research are Normative and Empirical, the normative approach is a document study, and Empirical research is one type of legal research that analyzes and examines the operation of law in society. The results of this study conclude that the registration of transfer of rights to land plots is held at the National Land Agency (BPN Sumbawa Regency) while the process of buying and selling land plots itself is held before a Notary / PPAT to obtain an authentic deed. and the process of transferring ownership rights to land plots that are traded, which includes using PPAT services, checking certificates to BPN, submitting proof of payment of SPPT PBB, submitting seller and buyer documents, signing the sale and purchase deed. The process of selling and buying before a Notary / PPAT is clear that there is legal security for the land plot being traded and gets legal protection in the event of a problem / dispute. Meanwhile, if the process of buying and selling land plots is carried out under the hand, then the lack of witnesses in the transaction process takes place because it is not through the presence of a Notary / PPAT.